Desenvolvimento e caracterização de um banho não-cianetado para a eletrodeposição de ligas de Cu-Sn-Zn: caracterização dos eletrodepósitos - Carvalho, Marcos Fernandes de (Universidade Federal de São Carlos, 2014)
The electrodeposition of Cu-Sn-Zn ternary alloys onto AISI 1010 steel from an acid bath with EDTA or NTA salts was investigated, with various proportions of the metal ions in the baths. The concentration of these metals in the baths was determined by factorial design of mixtures with pseudocomponents. From potentiometric titration of these baths were determined regression equations, which led to studies of variance analysis and of surface response. These studies allowed to a pH of stabilization of the Cu-Sn-Zn electrodeposition baths. The Cu-Sn-Zn voltammetric profile showed five cathodic regions: c1, c1 , c2, c3 and c4 (depending on bath composition), and the conditional potentials for the Cu2+, Sn2+ and Zn2+ complexes indicated that these regions were associated, respectively, with reduction of [CuY]2- complex to Cu; [Sn(H2O)6]2+ complex to Sn; [SnY]2- complex to Sn; H2O to H2; and [ZnY]2- complex to Zn. In the presence of NTA, [Cu(NTA)2]4- and [SnNTA]-, [Sn(NTA)2]4-; H2O and [ZnNTA]- and [Zn(NTA)2]4-, respectively, in the regions c1, c2, c3 and c4. Cu-Sn-Zn electrodeposits produced at Ed 1.70 V with qd 3.0 C cm−2 were characterized by EDS, SEM, XRD and confocal optical microscopy (COM) analysis. EDS indicated that a transition potential exists wherein a transition from Cu-Sn binary alloy to Cu-Sn-Zn ternary alloy occurred and, also, that Cu-Sn-Zn co-deposition was normal, preferential or anomalous depending on the bath composition. Moreover, this analyze showed that Zn reduction was facilitated in the presence of NTA. SEM of electrodeposits showed that they were formed by globular and/or irregular crystallites, and, in general, by clusters of crystallites of different sizes dispersed on this layer, depending on the bath composition. COM analysis showed that electrodeposit produced from NTA was more roughness than with EDTA. XRD pattern indicated that the Cu-Sn-Zn electrodeposits, depending on the composition of the baths, presented low crystallinity or crystalline structure with mixture of SnO, η- Cu6Sn5 and Cu5Zn8 phases or pure Sn, η-Cu6Sn5 and Cu5Zn8 phases. Multivariate analysis allows extracting the maximum relevant chemical information from the data.
Development and characterization of a non-cianyde bath for Cu- Sn-Zn alloys electrodeposition: characterization of the Cu-Sn-Zn electrodeposits
Keywords: Eletrodeposição; Ligas Cu-Sn-Zn; Planejamento fatorial de misturas; Microestrutura; Raios X - difração; Análise multivariada; CIENCIAS EXATAS E DA TERRA::QUIMICA